The handbook of fixed income securities - Fabozzi, Frank J.; Mann, Steven V. (Gale virtual reference library, 2005)
Comprehensive survey of current knowledge of global fixed income marketplace. Provides facts and formulas for finance professionals with emphasis on applications, electronics trading, and global portfolio management. Features contributions from leading academics and practitioners.